A New Malachite Damselfly (Synlestidae: Odonata) from the Eocene of Patagonia, Argentina - Petrulevicius, Julian Fernando (2018)
A new synlestid zygopteran, Madres delpueblo n. gen. n. sp., is described from the middle Eocene of Río Pichileufú, Patagonia, Argentina. The new genus is characterised by wing characters such as the discoidal cell narrow and long; Ax2 aligned with the arculus; MP distinctly curved after its origin; CuP+AA fused to the hind margin half of the length of the discoidal cell; CuP closer to Ax2 than to Ax1. Needle damselflies or Malachites are represented in other two Patagonian Eocene localities, by nymphs and adults. The new genus enlarges the fossil record of Lestomorpha in Argentina to four extinct genera: Promegalestes, Austroperilestes, Inacayalestes and Madres n. gen. versus two Recent ones: Lestes and Archilestes.